Intranasal Delivery of Camptothecin-Loaded Tat-Modified Nanomicells for Treatment of Intracranial Brain Tumors - Yuuki Takashima; Hiroaki Okada; Fuminari Akiyama; Takanori Kanazawa; Hiroyuki Taki (MDPI AG, 2012)
The blood-brain barrier is a substantial obstacle for delivering anticancer agents to brain tumors, and new strategies for bypassing it are sorely needed for brain tumor therapy. Intranasal delivery provides a practical, noninvasive method for delivering therapeutic agents to the brain. Intranasal application of nano-sized micelles that have been modified with Tat peptide facilitates brain delivery of fluorescent model materials. In this study, we evaluated a nose-to-brain delivery system for brain tumor therapy. We nasally administered the anti-tumor drug camptothecin (CPT) in solution and in methoxy poly(ethylene glycol) (MPEG)/poly(e-caprolactone) (PCL) amphiphilic block copolymers (MPEG-PCL) and cell penetrating peptide, Tat analog-modified MPEG-PCL (MPEG-PCL-Tat) MPEG-PCL-Tat to rats bearing intracranial glioma tumors and quantified the cytotoxicity against glioma cells, and the therapeutic effects. CPT-loaded MPEG-PCL-Tat micelles showed higher cytotoxicity than CPT-loaded MPEG-PCL. CPT-free MPEG-PCL-Tat didn't show any cytotoxicity, even at high concentrations (2 mmol/mL). CPT-loaded MPEG-PCL-Tat micelles significantly prolonged the median survival of rats. These results indicate that intranasal delivery of anti-cancer drugs with cell penetrating peptide-modified nanomicelles might be an effective therapy for brain tumors.